The Dynamic of Cheating: Descriptive Study of Intention to Cheat - Ilham Phalosa Reswara (Gadjah Mada Journal of Psychology (GamaJoP), 2020)
Cheating is strongly related to other unethical behaviors. It happens everywhere, including in universities. College students, ideally, should be prevented from cheating to minimize the potential of conducting unethical behaviors in the future. To design effective intervention, examining the cause of cheating is absolutely necessary. Cheating, like any other behavior, can be predicted by knowing its intention and the components of intention using the Theory of Planned Behavior. The present study explained the intention to cheat while studying in university along with its determinants and beliefs. The present study obtained data using online questionnaire based on the Theory of Planned Behavior to 233 participants. Regression analysis was performed to describe the significance level of each determinant and belief. The result showed that the determinant which had significant influence toward intention to cheat was attitude toward behavior (p = 0.00; β = 0.769; t = 15.620). The most significant belief in that determinant was “cheating during learning in university can help one earning good grade without studying hard”. Therefore, present study can be used as a basis to design interventions to reduce intention to cheat in university students.